THE INFLUENCE OF SOCIAL MEDIA MARKETING AND DIGITAL PAYMENT ON PURCHASE DECISION OF GEN Z AT MSMEs SUNBAE KAWASAN MEGAMAS MANADO - Sangeroki, Rafael; Gunawan, Emilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
In the modern digital era, digitalization plays a crucial role in daily life, especially in business activities. Among its key components, social media marketing and digital payments have become important tools for businesses to remain competitive and adaptable. Both approaches not only improve efficiency but also create opportunities for innovation and market expansion, particularly for MSMEs. This research investigates the effect of social media marketing and digital payments on the purchasing decisions of Gen Z at MSMEs in Sunbae Kawasan Megamas Manado. Using a quantitative method, data were collected from 100 respondents via Google Forms. The results show that both variables significantly influence purchase decisions, emphasizing the need for MSMEs to adopt these digital tools to better engage young consumers, strengthen competitiveness, and increase sales in today’s dynamic business environment.   Keywords: Social Media Marketing, Digital Payment, Purchase Decision